2014
DOI: 10.1126/scisignal.2004479
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Methylation of CRTC2 Is Critical in the Transcriptional Control of Hepatic Glucose Metabolism

Abstract: Fasting glucose homeostasis is maintained in part through cAMP (adenosine 3',5'-monophosphate)-dependent transcriptional control of hepatic gluconeogenesis by the transcription factor CREB (cAMP response element-binding protein) and its coactivator CRTC2 (CREB-regulated transcriptional coactivator 2). We showed that PRMT6 (protein arginine methyltransferase 6) promotes fasting-induced transcriptional activation of the gluconeogenic program involving CRTC2. Mass spectrometric analysis indicated that PRMT6 assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Choi et al reported that PRMT1 increases hepatic gluconeogenesis by inhibiting protein kinase B (Akt)-mediated FoxO1 phosphorylation [4]. Han et al reported that PRMT6 promotes fasting-induced hepatic gluconeogenesis via CREB-regulated transcriptional coactivator 2 (CRTC2) methylation [5]. Moreover, we found that PRMT1 and PRMT3 are involved in hepatic lipogenesis [6,7].…”
Section: Introductionmentioning
confidence: 80%
“…Choi et al reported that PRMT1 increases hepatic gluconeogenesis by inhibiting protein kinase B (Akt)-mediated FoxO1 phosphorylation [4]. Han et al reported that PRMT6 promotes fasting-induced hepatic gluconeogenesis via CREB-regulated transcriptional coactivator 2 (CRTC2) methylation [5]. Moreover, we found that PRMT1 and PRMT3 are involved in hepatic lipogenesis [6,7].…”
Section: Introductionmentioning
confidence: 80%
“…Co-IP is a well-established approach for identifying kinase substrates, and has recently been applied to both arginine and lysine methyltransferases 9; 50 . A major advantage of this approach is that it captures enzyme/substrate interactions that may require scaffold proteins or interactions through other biomolecules such as DNA or RNA.…”
Section: Proteome-wide Approaches For Identifying Methyltransferase Amentioning
confidence: 99%
“…Arginine methylation has many critical functions such as in signal transduction 4 , regulation of mRNA splicing and translation 5 , and physiological processes such as glucose homeostasis 6 (reviewed in 7; 8; 9 ). Non-histone lysine methylation regulates pathways including tumor suppression by p53 and signaling by NFκB 10; 11 (reviewed in 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, several lines of evidence have shown the importance of type I PRMTs in the liver, as they are responsible for hepatic glucose metabolism. Choi et al (17) and Han et al (18) reported that PRMT1 and PRMT6 regulate hepatic gluconeogenesis. Lee et al (19) also demonstrated an increased ADMA plasma concentration and decreased hepatic PRMT1 expression in diabetic mice (db/db), suggesting that PRMTs play an important role in the onset of diabetes in the liver.…”
mentioning
confidence: 99%